Institutional Maintenance of Cross-Border Projects Monitoring - Tsisinska, Oksana; Tsybulska, Yulia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
The role of cross-border projects’ monitoring in increasing of the grant funds efficiency, local budgets targeting and ensuring of the regional competitiveness is represented. The obstacles in implementing of monitoring system in Ukraineare are determined by a lot of factors. Options of the Ukrainian regions monitoring organization are examined. Functions of the responsible for cross-border projects monitoring authority are determined.

W artykule pokazano rolę monitorowania projektów transgranicznych w zwiększaniu efektywności funduszy dotacyjnych, budżetów lokalnych i zapewnieniu konkurencyjności regionalnej. Wykryte przeszkody w realizacji systemu monitoringu na Ukrainie są zdeterminowane wieloma czynnikami. W artykule zaprezentowane zostały również opcje organizacyjne monitorowania tych działań w różnych regionach Ukrainy. Ponadto przedstawiono funkcje organów nadzoru odpowiedzialnych za monitorowanie transgranicznych projektów.